PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM SUPERVISI PEMBELAJARAN DI SEKOLAH DASAR - Darmanto Darmanto; Karso Karso (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The development and use of Information and Communication Technology (ICT) in education can make reforms for a better education system. Current conditions at SDN 7 Rimau Island, Pulau Rimau sub-district, Banyuasin District, teachers face several difficulties in applying (ICT) in the teaching and learning process in schools, due to the absence of infrastructure such as computer laboratories, and mastery of ICT from teachers. Implementation of ICT guidance, training for teachers at SDN 7 Pulau Rimau in Pulau Rimau sub-district by providing knowledge and use of ICT in the learning process. The methods used are: lectures, discussions, and training. The application that is taught is flash, e-learning, management system learning is only an introduction and deeper in Microsoft Word. After attending this training, the teacher has the knowledge and understanding of the diversity of ICT applications. In addition, great motivation arises from the teacher to be able to control and optimize the use of ICT for teaching and learning in the classroom.